2015
DOI: 10.1902/jop.2015.150319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MicroRNA‐146a and Its Targets in Gingival Tissues of Patients With Chronic Periodontitis

Abstract: Patients with CP had higher levels of miR-146a than healthy individuals, accompanied by reduced levels of TNF-α and IL-6. A positive relationship between miR-146a levels and clinical parameters suggests a pathophysiologic role of miR-146a in CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 43 publications
9
86
3
Order By: Relevance
“…Our results demonstrated a massively increased expression of miR‐146a in the periodontal tissues obtained from patients with GAgP during surgical treatment. Consistently, we also observed increased expression of miR‐146a in patients with the chronic form of periodontitis . Of course, given the difference in nature of these two diseases, comparison of the results is not logical.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our results demonstrated a massively increased expression of miR‐146a in the periodontal tissues obtained from patients with GAgP during surgical treatment. Consistently, we also observed increased expression of miR‐146a in patients with the chronic form of periodontitis . Of course, given the difference in nature of these two diseases, comparison of the results is not logical.…”
Section: Discussionsupporting
confidence: 76%
“…According to the SD values observed in similar research, sample sizes for the groups of patients and healthy controls were estimated using the following statistical formula:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that miR-146a and miR-155 are present in periodontal tissues, and because activation of macrophages is strongly dependent on their presence(Jablonski, Gaudet, Amici, Popovich, & Guerau-de-Arellano, 2016;O'Connell, Taganov, Boldin, Cheng, & Baltimore, 2007), it could be assumed that inflammatory cells along with periodontal tissue cells and systemic circulation represent possible sources of these miRNAs in GCF.Present results show that in non-diabetic and type 2 diabetic periodontitis patients, miR-146a and miR-155 show significantly higher levels compared with periodontally healthy and that nonsurgical periodontal therapy significantly reduced expression levels of both miRs in GCF reflecting the reduction in periodontal inflammation observed clinically. In the previous studies,Motedayyen et al (2015) showed upregulation of miR-146a in the gingiva of patients with chronic periodontitis whileXie et al (2011) showed upregulation of miR-146a and downregulation of miR-155 levels in human inflamed gingival tissues collected during periodontal flap surgery and suggested a complex role of these miRs in gingival inflammation. based on ROC curves analysis pointing at better performance of miR-146a in non-diabetic, and miR-155 in type 2 diabetic patients.…”
mentioning
confidence: 89%
“…In this research, we focused on the two immunomodulatory miRs, miR-146a and miR-155, which are co-induced in many cell types responding to microbial lipopolysaccharide, facilitating a negative feedback control of NFkB target genes which encode various mediators of inflammation (Ma, Becker Buscaglia, Barker, & Li, 2011;Taganov, Boldin, Chang, & Baltimore, 2006) and involved in oxidative stress by targeting superoxide dismutase (SOD) (Ji et al, 2013). Noteworthy, periodontitis patients had higher gingival tissue levels of miR-146a accompanied with the reduced levels of inflammatory cytokines than healthy (Motedayyen, Ghotloo, Saffari, Sattari, & Amid, 2015). We aimed to quantify expression levels of miR-146 and miR-155 in gingival crevicular fluid obtained from non-diabetic and type 2 diabetic periodontitis patients, at baseline and after non-surgical periodontal treatment to examine their association with periodontal status as well as oxidative stress.…”
mentioning
confidence: 99%